Pengaruh Keputusan Investasi dan Kebijakan Dividen Terhadap Nilai Perusahaan Melalui Kinerja Keuangan Pada Perusahaan Lq-45 Tbk Tahun 2020-2022 - Dewianti Dwi Wahyuni; Chamariyah Chamariyah; Wasis Budiarto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Dewianti Dwi Wahyuni, 2024. The Influence of Investment Decisions and Dividend Policy on Company Value, Financial Performance in Companies Through Financial Performance in LQ-45 Tbk in 2020-2022. Wijaya Putra University Postgraduate Program Surabaya. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 31 companies. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) For describes the nature of investment, dividend policy, company value and financial performance in LQ 45 Tbk in 2020-2022; 2) For tested and analyzed the significant influence of investment ownership on the company value of LQ 45 Tbk in 2020-2022; 3) Uintuik tested and analyzed the significant influence of investment intelligence on the financial performance of LQ 45 Tbk in 2020-2022; 4) For tested and analyzed the significant influence of dividend policy on the financial performance of LQ 45 Tbk in 2020-2022; 5) For tested and analyzed the significant influence of dividend policy on company value in LQ 45 Tbk in 2020-2022; 6) For tested and analyzed the significant influence of financial performance on the company value of the LQ 45 Tbk for 2020-2022; 7) For tested and analyzed the significant influence of investment profitability on company value through financial performance in LQ 45 Tbk in 2020-2022; 8) For tested and analyzed the significant influence of dividend policy on company value through the financial performance of LQ 45 Tbk 2020-2022. The research results show that: 1) investment decisions have no significant effect on company value. 2) investment decisions have no significant effect on financial performance. 3) dividend policy has no significant effect on financial performance. 4) dividend policy has no significant effect on company value. 5) financial performance has no significant effect on company value. 6) investment decisions have no significant effect on company value. 7) dividend policy has no significant effect on company value which is mediated by financial performance.